Лексикографічна концепція англо-українського семантико-словотвірного словника - Гороть, Є. І.; Малімон, Леся Костянтинівна; Horot, Ye. I.; Malimon, Lesia K. (Східноєвропейський національний університет ім. Лесі Українки, 2011)
У статті описані принципи укладання англо-українського семантико-словотвірного словника на матеріалі загальнолітературної мови. The article presents the main principles of compiling an English-Ukrainian Semantic- Word-Building Dictionary on the material of the general literary language.
Lexicographical Conception of Compiling an English-Ukrainian Semantic- Wordbuilding Dictionary
Keywords: семантико-словотвірне гніздо; акт словотворення; напрям похідності; словотворчий засіб; семантичне ядро; твірна основа; semantic-word-building word family; the act of wordbuilding; the direction of derivation; wordbuilding means; semantic nucleus; producing stem